(Ø§Ù„ØØ±ÙƒØ© Ø§Ù„Ù…ÙˆØ¶Ø¹ÙŠØ© ÙÙŠ Ø§Ù„Ø®Ø·Ø§Ø¨ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠ ÙˆØ£Ø«Ø±Ù‡Ø§ ÙÙŠ Ø§Ù„Ø¯Ù„Ø§Ù„Ø© (Ø¯Ø±Ø§Ø³Ø© Ø¨Ù„Ø§ØºÙŠØ© ØªØÙ„ÙŠÙ„ÙŠØ© - Abdelrahman Moawad Ali; Ragab Ibrahim Ahmed Awad; Elsayed Mohamed Salem Alawadi (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2021)
Ù„Ø§ Ø´Ùƒ Ø£Ù† Ø±ØµØ¯ Ø§Ù„Ø®ÙˆØ§Øµ Ø§Ù„ØªØ±ÙƒØ¨ÙŠØ© Ù„ØµÙŠØ§ØºØ© Ø§Ù„Ø®Ø·Ø§Ø¨ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠ ÙŠØ³Ø§Ø¹Ø¯ Ø¹Ù„Ù‰ Ø§Ù„ÙˆØµÙˆÙ„ Ø¥Ù„Ù‰ Ø§Ù„Ø¯Ù„Ø§Ù„Ø©ØŒ ÙˆÙ„Ø§ Ø£Ø¹Ù†ÙŠ Ø¨Ø§Ù„Ø¯Ù„Ø§Ù„Ø© Ù‡Ù†Ø§ Ø§Ù„Ù†Ø§ØªØ¬ Ø§Ù„Ø£ÙˆÙ„ Ù…Ù† Ø§Ù„ØµÙŠØ§ØºØ©Ø› Ù„Ø£Ù† Ù‡Ø°Ø§ Ø§Ù„Ù†Ø§ØªØ¬ ÙŠØªØÙ‚Ù‚ ØºØ§Ù„Ø¨Ø§Ù‹ ÙÙŠ Ø£ÙŠ Ù…Ø³ØªÙˆÙ‰ ØªØ±ÙƒÙŠØ¨ÙŠØŒ Ø¬Ø§Ø¡Øª Ø§Ù„ØµÙŠØ§ØºØ© ÙÙŠÙ‡ Ø¹Ù„Ù‰ Ø§Ù„Ù†Ù…Ø· Ø§Ù„Ù…Ø£Ù„ÙˆÙØŒ ÙˆØ¥Ù†Ù…Ø§ Ø£Ø¹Ù†ÙŠ Ø§Ù„Ù†Ø§ØªØ¬ Ø§Ù„Ø«Ø§Ù†ÙŠØŒ Ø£Ùˆ Ù…Ø§ Ø£Ø·Ù„Ù‚ Ø¹Ù„ÙŠÙ‡ Ø¹Ø¨Ø¯ Ø§Ù„Ù‚Ø§Ù‡Ø± Ø§Ù„Ø¬Ø±Ø¬Ø§Ù†ÙŠ (Ø§Ù„Ù…Ø¹Ø§Ù†ÙŠ Ø§Ù„Ø«ÙˆØ§Ù†ÙŠ) Ø§Ù„ØªÙŠ Ù„Ø§ ØªØ¨Ø±Ø² Ø¥Ù„Ù‰ ØÙŠØ² Ø§Ù„Ø¥Ø¯Ø±Ø§Ùƒ Ø§Ù„Ø¹Ù‚Ù„ÙŠ Ø¥Ù„Ø§ Ø¹Ù†Ø¯Ù…Ø§ ØªØªÙ„ÙˆÙ† Ø§Ù„ØµÙŠØ§ØºØ© Ø¨Ø¥Ù…ÙƒØ§Ù†Ø§Øª ØªØ¹Ø¨ÙŠØ±ÙŠØ©ØŒ ÙˆØªØØ±ÙƒØ§Øª ØªØ±ÙƒÙŠØ¨ÙŠØ©ØŒ ÙˆÙ…Ù† Ø§Ù„Ù…Ø¤ÙƒØ¯ Ø£Ù† (Ø§Ù„Ù…Ù‚Ø§Ù…) ÙŠÙ…Ø«Ù„ Ø£Ø³Ø§Ø³ Ø§Ù„Ø¯Ù„Ø§Ù„Ø©ØŒ ÙˆØ§ÙØªÙ‚Ø§Ø¯Ù‡ ÙŠØ¤Ø¯ÙŠ Ø¥Ù„Ù‰ ÙˆØ±ÙˆØ¯ Ù…ÙØ±Ø¯Ø§Øª Ù…ØªÙ†Ø§Ø«Ø±Ø© Ù„Ø§ ØªØÙƒÙ…Ù‡Ø§ Ø¹Ù„Ø§Ù‚Ø© Ù…Ø§Ø› Ù„Ø£Ù†Ù‡Ø§ Ù„Ù… ØªØ±ØªØ¨Ø· Ø¨Ù…Ù‚Ø§Ù… ÙŠØ±Ø¨Ø· Ø¨ÙŠÙ† Ø¹Ù†Ø§ØµØ±Ù‡Ø§ØŒ ÙˆØ¹Ù„Ù‰ Ù‡Ø°Ø§ ÙØ¥Ù† Ø£ÙŠØ© Ø¹Ù…Ù„ÙŠØ© ØªØÙ„ÙŠÙ„ÙŠØ© Ù„Ù„ØµÙŠØ§ØºØ© Ù„Ù† ØªÙƒÙˆÙ† Ù…ÙØ¬Ø¯ÙÙŠØ©Ø› Ù„Ø£Ù†Ù‡ Ù…Ù† Ø§Ù„Ø¶Ø±ÙˆØ±ÙŠ ØªØµÙˆØ± Ø§Ù„Ù…Ù‚Ø§Ù… Ø¨Ù‡Ø°Ø§ Ø§Ù„ØªØÙ„ÙŠÙ„ØŒ ÙˆÙ…Ø¹ ØªØµÙˆØ± Ù‡Ø°Ø§ Ø§Ù„Ù…Ù‚Ø§Ù… ØªØ£Ø®Ø° Ø§Ù„ØµÙŠØ§ØºØ© Ø£Ø´ÙƒØ§Ù„Ø§Ù‹ Ù…ØªÙ…Ø§ÙŠØ²Ø© ÙÙŠ ØØ±ÙƒØªÙ‡Ø§ Ø§Ù„ØªØ±ÙƒÙŠØ¨ÙŠØ©ØŒ ØÙŠØ« ØªÙ…ØªØ¯ ÙÙŠ Ø§ØªØ¬Ø§Ù‡Ø§Øª Ù…Ø®ØªÙ„ÙØ© Ù…Ù†Ù‡Ø§ Ù…Ø§ ÙŠØ°Ù‡Ø¨ Ø·ÙˆÙ„Ø§ØŒ ÙˆÙ…Ù†Ù‡Ø§ Ù…Ø§ ÙŠØ°Ù‡Ø¨ Ø¹Ø±Ø¶Ø§ ÙˆÙ…Ù†Ù‡Ø§ Ù…Ø§ ÙŠØ£Ø®Ø° Ø¹Ù…Ù‚Ø§ Ù…ÙˆØ¶Ø¹ÙŠØ§Ù‹ØŒ ÙˆÙ‡Ùˆ Ù…Ø§ Ø¢Ø«Ø±Øª ØªØ³Ù…ÙŠØªÙ‡ Ù‡Ù†Ø§Â  Ø¨Ø§Ù„ØØ±ÙƒØ© Ø§Ù„Ù…ÙˆØ¶Ø¹ÙŠØ©. ÙˆÙ„Ø§ Ø´Ùƒ Ø£Ù† ØªØªØ¨Ø¹ Ø£Ø«Ø± ØªÙ„Ùƒ Ø§Ù„ØØ±ÙƒØ§Øª ÙŠØ¹ÙŠÙ† Ø¹Ù„Ù‰ ÙÙ‡Ù… Ø¯Ù„Ø§Ù„Ø© Ø§Ù„Ø®Ø·Ø§Ø¨ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠ. Ù…Ù† Ù‡Ù†Ø§ Ø¬Ø§Ø¡Øª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù…ÙˆØ³ÙˆÙ…Ø©: "Ø§Ù„ØØ±ÙƒØ© Ø§Ù„Ù…ÙˆØ¶Ø¹ÙŠØ© ÙÙŠ Ø§Ù„Ø®Ø·Ø§Ø¨ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠ ÙˆØ£Ø«Ø±Ù‡Ø§ ÙÙŠ Ø§Ù„Ø¯Ù„Ø§Ù„Ø©ØŒ Ø¯Ø±Ø§Ø³Ø© Ø¨Ù„Ø§ØºÙŠØ© ØªØÙ„ÙŠÙ„ÙŠØ©". ÙˆÙ‚Ø¯ Ù‚Ø³Ù…Øª Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¨Ø¹Ø¯ Ø§Ù„Ù…Ù‚Ø¯Ù…Ø© Ø¥Ù„Ù‰ Ù…Ø¨ØØ«ÙŠÙ† ØªØªÙ„ÙˆÙ‡Ù…Ø§ Ø®Ø§ØªÙ…Ø©ØŒ ÙˆØ°Ù„Ùƒ Ø¹Ù„Ù‰ Ø§Ù„Ù†ØÙˆ Ø§Ù„ØªØ§Ù„ÙŠ: Ø§Ù„Ù…Ø¨ØØ« Ø§Ù„Ø£ÙˆÙ„: ÙˆÙ‡Ùˆ Ø¨Ø¹Ù†ÙˆØ§Ù† "Ø®ØµØ§Ø¦Øµ Ø§Ù„Ø®Ø·Ø§Ø¨ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠ" ÙˆÙŠÙØ³ØªÙ‡Ù„ Ø¨Ø¥Ø·Ù„Ø§Ù„Ø© ØÙˆÙ„ Ù…Ø¹Ù†Ù‰ Ø§Ù„Ø®Ø·Ø§Ø¨ ÙˆØ£Ù†ÙˆØ§Ø¹Ù‡ØŒ Ø«Ù… Ø¹Ø±Ø¶ Ù„Ù…Ø§ ØªÙ…ÙŠØ² Ø¨Ù‡ Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„Ø®Ø·Ø§Ø¨ ÙÙŠ Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… Ù…Ù† Ø³Ù…Ø§Øª ÙˆØ®ØµØ§Ø¦Øµ Ø¹Ø§Ù…Ø©. Ø§Ù„Ù…Ø¨ØØ« Ø§Ù„Ø«Ø§Ù†ÙŠ: ÙˆÙ‡Ùˆ Ø¨Ø¹Ù†ÙˆØ§Ù† " Ø§Ù„ØØ±ÙƒØ© Ø§Ù„Ù…ÙˆØ¶Ø¹ÙŠØ©" ÙˆÙ‚Ø¯ ØØ§ÙˆÙ„Øª ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ù…Ø¨ØØ« Ø±ØµØ¯ Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø§Ù„Ù…Ø¨ØªØ¯ÙŠØ© Ø¨ÙŠÙ† Ø§Ù„ØØ±ÙƒØ© Ø§Ù„Ù…ÙˆØ¶Ø¹ÙŠØ©ØŒ ÙˆØ§Ù„Ø®Ø·Ø§Ø¨ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠ ÙˆÙ…Ø¹Ø²Ù‰ Ù‡Ø°Ù‡ Ø§Ù„Ø¹Ù„Ø§Ù‚Ø©. Ø§Ù„Ø®Ø§ØªÙ…Ø©: ÙˆØªØ¶Ù… Ø£Ù‡Ù… Ù…Ø§ ØªÙˆØµÙ„ Ø¥Ù„ÙŠÙ‡ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù…Ù† Ù†ØªØ§Ø¦Ø¬ . ÙˆÙ‚Ø¯ Ø£Ø«Ø¨ØªÙ‘Ù ÙÙ‰ Ù†Ù‡Ø§ÙŠØ© Ø§Ù„Ø¨ØØ« Ù‚Ø§Ø¦Ù…Ø© Ø¨Ø§Ù„Ù…ØµØ§Ø¯Ø± ÙˆØ§Ù„Ù…Ø±Ø§Ø¬Ø¹ Ø§Ù„ØªÙ‰ Ø§Ø¹ØªÙ…Ø¯Øª Ø¹Ù„ÙŠÙ‡Ø§ ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ«.There is no doubt that observing the compositional properties of the formulation of the Qurâ€™anic discourse helps to reach the significance. I do not mean by significance here the first product of the formulationÂ  Because this result is often achieved at any compositional level, the wording in it came in the familiar pattern, but I mean the second product, or what Abdel-Qaher Al-Jarjani called (the meanings of seconds) that does not emerge into the realm of mental perception except when the wording is colored with expressive capabilities, synthetic movements, and fromÂ  It is certain that (the maqam) represents the basis of significance, and lacking it leads to the emergence of dispersed vocabulary that is not governed by some relationshipÂ  Because it is not related to a denominator that links its elements, and therefore any analytical process of the formulation will not be feasible.Â  Because it is necessary to visualize the maqam with this analysis, and with the perception of this maqam, the formulation takes distinct forms in its compositional movement, as it extends in different directions, some of which go in length, some of which go in width, and some of them take a local depth, which is what I prefer to call here the local movement.Â  There is no doubt that tracking the impact of these movements helps to understand the significance of the Qurâ€™anic discourse. Hence this study tagged: â€œThe local movement in the Qurâ€™anic discourse and its impact on significance, an analytical rhetorical study.â€After the introduction, this research was divided into two topics that are followed by a conclusion, as follows: The first topic: It is titled â€œCharacteristics of the Qurâ€™anic Discourseâ€ and begins with an overview of the meaning and types of discourse, and then presents the general characteristics and characteristics of the discourse style in the Holy Qurâ€™an. The second topic: It is entitled "Local Movement". I tried in this section to monitor the primary relationship between positional movement, and the Qur'anic discourse and the significance of this relationship. Conclusion: It includes the most important results of this research. At the end of the research, a list of the sources and references that I relied on in this research was established.